Are infants exposed to antimicrobials during the first 3 months of life at increased risk of recurrent use? An explorative data-linkage study. (9th February 2022) - Thaulow, Christian Magnus; Harthug, Stig; Nilsen, Roy Miodini; Eriksen, Beate Horsberg; Wathne, Jannicke Slettli; Berild, Dag; Blix, Hege Salvesen
Abstract: Objectives: To investigate whether infants exposed to antimicrobials in hospital during the first 3 months of life had an increased risk of ambulatory antimicrobial use during the following year compared with infants not exposed to antimicrobials during the first 3 months of life. Methods: Norwegian cohort study of infants less than 3 months consisting of one group exposed to antimicrobials recruited during hospitalization and one group not exposed to antimicrobials. Ten unexposed infants were matched with one exposed infant according to county of residence, birth year and month, and sex. The Norwegian Prescription Database was applied to register antimicrobial use from the month after discharge and 1 year onward. We defined comorbidity based on antimicrobials prescribed as reimbursable prescriptions due to underlying diseases. Results: Of 95 infants exposed to antimicrobials during the first 3 months of life, 23% had recurrent use compared with 14% use in 950 unexposed infants [relative risk (RR) = 1.7 (95% CI = 1.1–2.5) and comorbidity-adjusted RR = 1.4 (95% CI = 0.9–2.2)]. The recurrence use rate in exposed term infants (≥37 weeks, n = 70) was 27% compared with 12% in their unexposed matches [RR 2.3 = (95% CI = 1.4–3.7) and comorbidity-adjusted RR = 1.9 (95% CI = 1.2–3.2). Of 25 exposed preterm infants, 3 (12%) had recurrent use. The total antimicrobial prescription rate was 674/1000 in the exposed group and 244/1000 in the unexposed group [incidence rate ratio = 2.8 (95% CI = 1.6–4.9)]. Conclusions: Infants exposed to antimicrobials during the first 3 months of life had an increased risk of recurrent use during the following year. This increased risk also appeared in term infants without infection-related comorbidity.